(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Bacillus sp. are widely used for isolating these protease enzymes. In this project, organisms were isolated from the soil sample was identified by morphological and biochemical characterization as Bacillus sp. The bacterial isolates were sub-cultured in Casein agar plates by quadrant streaking. Large amount of the enzymes was produced using fermentation process.Enzyme crude extract was prepared by centrifuging the fermented broth at 4500 rpm for 15 minutes at 4ºC. The precipitation method using ammonium sulphate was used to complete the crude enzyme partial purification. Partial purified enzyme showed maximum zones., when compared to the crude activity of the enzyme..The protein content was estimated by Bradford assay and was found to be 7.0µg/ml and 13.0µg/ml for crude and partially purified enzyme respectively. In this review reported that bacteria from soil environment, bacillus sps. Which acted as a source of protease.